First, 9.8 (Gravity) times 3 (time) equals 29.4, which is the velocity after 3 seconds. The kinematic equation for change in position that uses the variables we have is:
delta x= (v)(t) -0.5(acceleration)(time)^2
delta x= 29.4 times (3) - 0.5 (9.8) times 9
delta x= 44.1
100 minus 44.1 equals 55.9, which is the answer for part a.
Tell me if you need any clarification
PART B:
The kinematic equation for this is:
delta x= (initial velocity) times time plus 0.5 (a)(time)^2
100=(0)times(x) plus 0.5 (a)(time)^2
100=0.5(9.8)(x)^2
100=4.9x^2
100/4.9 is approxamitely 20.4.
The squareroot of this is approxamitely 4.5.
4.5 seconds
Tell me if you need any clarification
Answer:
x = 6
Step-by-step explanation:
Isolate the variable by dividing each side by factors that don't contain the variable.
Answer:
$2.72
Step-by-step explanation:
The increase from last week is the fraction ...
(new price)/(old price) -1 = (1.82/1.65) -1 = 17/165
so the amount of increase Sally will pay this week is ...
17/165×$26.40 = $2.72
_____
<em>Comment on the working</em>
We could work this several ways. Perhaps most straightforward would be to determine how many gallons Sally bought last week, and multiply that by the change in price. Or, the number of gallons could be multiplied by the new price per gallon and the difference from the old purchase amount found.
If you look at the numbers, you see that we have effectively done it the first way. The change in price is $0.17 per gallon, and the number of gallons Sally bought is $26.40/$1.65.
0.584 is greater than 0.58 !